Correlation between Vitamin D and Urine Microalbumin among Patients with Diabetic Nephropathy: A Cross-sectional Study - Saka Prasanna; Patil B Preethi (Journal of Clinical and Diagnostic Research)
Introduction: Diabetic nephropathy is characterised by microalbuminuria (30-300 mg/day). Vitamin D is thought to affect pathophysiology of diabetes mellitus through vitamin D receptor activation or by regulating calcium homeostasis, thus contributing to development of diabetes mellitus and its complications in deficiency status. Aim: To study the relationship between vitamin D levels and urine microalbumin among individuals with type 2 diabetes mellitus, both with and without diabetic nephropathy. Materials and Methods: This was an analytical cross-sectional study conducted in Department of Biochemistry and Nephrology, JJM Medical College, Davangere, Central Karnataka, India, between January 2019 and January 2020, involving 150 subjects: 50 with Type 2 Diabetes Mellitus (T2DM) without nephropathy, 50 with T2DM with nephropathy, and 50 healthy individuals. Glycaemic control of subjects was estimated using Glycosylated Haemoglobin (HbA1c), and renal damage was screened with serum creatinine, vitamin D, and urine microalbumin levels. The comparison of HbA1c, serum creatinine, microalbumin in urine, and vitamin D was analysed by Kruskal-Wallis test, while the association between vitamin D and HbA1c, and its correlation with microalbumin, was analysed by Spearman’s correlation. Results: The median age of controls and type 2 diabetics without nephropathy was 48 years, compared to 56 years among subjects with nephropathy, and the difference was statistically significant. A male preponderance was observed in all groups: 33 (66%) among type 2 diabetics without nephropathy, 34 (68%) among nephropathy subjects, and 36 (72%) among controls. The median concentrations of HbA1c, creatinine, and microalbumin were higher in diabetic nephropathy (8, 2.4, 140) compared to subjects without nephropathy (7, 1.16, 17) and controls (5.9, 1, 14). The median concentration of serum vitamin D was lower in diabetic nephropathy (12) compared to subjects without nephropathy (18) and controls (31). Furthermore, vitamin D and HbA1c were reciprocally related among diabetic nephropathy subjects (r=-0.61, p<0.001). In contrast, HbA1c and microalbumin were positively correlated (r=0.73, p<0.001). Conclusion: There is a substantial correlation between glycemic control, in the form of HbA1c and renal damage, in the form of microalbumin, and vitamin D levels. This justifies the inclusion of vitamin D as a potential new screening tool for diabetic nephropathy along with microalbumin.